English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-07 07:55:14 · 2 answers · asked by dmoney 1 in Science & Mathematics Mathematics

2 answers

y= ln(3x)
e^y = 3x
x=(e^y)/3
so the inverse function is:
f^{-1}(y) = (e^y)/3 .

2007-01-08 14:25:28 · answer #1 · answered by tablecloth 1 · 2 0

Set the equation equal to y:

y = ln(3x)

Then to find the inverse, swap all x's with y's and vice versa:

x = ln(3y)

Then solve for y, first by raising both sides to the power of e. (e and ln are inverse functions; e^(ln x) = x)

e^x = 3y

Divide by 3:

e^x/3 = y

And that's your answer. The inverse of ln(3x) is 1/3e^(3x).

2007-01-07 16:01:58 · answer #2 · answered by Jim Burnell 6 · 1 0

fedest.com, questions and answers